Replacing sedentary time with physical activity: effects on health-related quality of life in older Japanese adults - Akitomo Yasunaga; Ai Shibata; Kaori Ishii; Shigeru Inoue; Takemi Sugiyama; Neville Owen; Koichiro Oka (Health and Quality of Life Outcomes, 2018)
Abstract Background The isotemporal substitution (IS) approach can be used to assess the effect of replacing one activity with the equal duration of another activity on relevant outcomes. This study examined the associations of objectively assessed sedentary behavior (SB) and physical activity (PA) with health-related quality of life (HRQOL) in older Japanese adults, using the IS approach. Methods Participants were 287 older Japanese adults (aged 65–84 years) who wore accelerometers for at least 7 days. We calculated the average daily time spent in SB (≤1.5 METs); light-intensity PA (LPA: > 1.5 to < 3.0 METs); and moderate- to vigorous-intensity PA (MVPA: ≥3.0 METs) per day. HRQOL was assessed using the Medical Outcomes Survey Short Form-8 questionnaire. Results The IS models showed replacing SB or LPA with MVPA to be significantly associated with better physical component summary scores. Replacing SB with MVPA was marginally associated with better mental component summary scores. Conclusion These findings indicate that replacing SB with the same amount of MVPA may contribute to better physical HRQOL in older adults.